TINJAUAN KONSTITUSIONAL PASAL 27A UU ITE TERKAIT KRITIK PUBLIK: PROBLEMATIKA FRASA 'ORANG LAIN' DAN PERLINDUNGAN KEBEBASAN BERPENDAPAT DI RUANG DIGITAL - Timbo Mangaranap Sirait; Nungky Sendias (LPPM STIH Awang Long, 2025)
Law continually evolves in response to social developments within society; as a result, its norms often become counterproductive in their enforcement. This study employs a normative legal research method through a literature review to examine and conclude the following: this review synthesizes constitutional law research analyzing Article 27A of the Electronic Information and Transactions Law (UU ITE), with a particular focus on the phrase “another person” (orang lain) and its implications for freedom of expression in the digital sphere. The analysis seeks to address legal ambiguity and its impact on digital rights in Indonesia. Accordingly, the provision is evaluated through relevant Constitutional Court decisions concerning the phrase “another person,” assessing judicial and doctrinal responses to restrictions on freedom of expression, examining compliance with human rights standards, analyzing the consistency of law enforcement, and exploring prospects for legal reform. The findings reveal persistent ambiguity in the phrase “another person,” resulting in multiple interpretations and legal uncertainty, despite judicial efforts to narrow the scope of defamation to individuals. While these efforts enhance legal clarity and reduce arbitrary enforcement, the provision is deemed conditionally unconstitutional and lacking binding legal force insofar as it is not interpreted to mean “excluding government institutions, groups of persons with specific or identifiable identities, institutions, corporations, professions, or public offices.